Bridging the Gap: Facilitating Genealogical Research. Issue 1 (2nd January 2018) - Bremer, Peter
ABSTRACT: Libraries can help support genealogy research in our communities by providing resources and expertise. Reaching out to local family historians and presenting useful information can be one of the best ways to meet the needs of this group.